The Impact of Bitcoin Halving Day on Stock Market in Indonesia - Muhammad Harits Zidni Khatib Ramadhani; Yana Ulfah; Muhammad Rinaldi (Journal of International Conference Proceedings (JICP), 2022)
This study aims to determine the impact of the bitcoin halving day phenomenon that occurred on May 11, 2020, on abnormal return and trading volume activity on listed firms of index LQ45 on the Indonesia Stock Exchange. At the bitcoin halving day, there was a jump in the price of bitcoin and other cryptocurrencies. Based on the event theory, the researcher wanted to find out whether capital market investors in Indonesia tend to switch investment instruments to the cryptocurrency market with this phenomenon. These data were taken weekly for four weeks before the halving and four weeks after the 5-month halving. Using the Paired sample T-test to determine whether there is a difference in abnormal return and trading volume. The results showed that there was a significant difference between stock price’s abnormal return and trading volume before the halving day and after the bitcoin halving day. The abnormal return did not increase, but the trading volume decreased, which is thought to be due to the halving day